Human-Specific Adjectives in Al-Azhari's Refinement Of Language: A Lexicographical And Semantic Study/ النعوتُ الخاصةُ بالإنسانِ في تهذيب اللغة للأزهري: دراسة معجمية دلالية - Ahmed Kemis Saad; Ali Matar Jr (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study aims to identify the attributes specific to humans in the lexicon Tahdhib al-Lugha by al-Azharī, as well as to examine the semantic significance of these terms among early and later scholars and to compare between them. It also investigates whether al-Azharī was unique in assigning these particular attributes, and what role these terms play in serving the Arabic language in our present time. The study employs the descriptive-analytical approach, wherein I present the issue as found in al-Tahdhib, then examine it, trace the views of early scholars on it, compare them with those of later scholars and their statements, assess the validity of their opinions, and connect them to the contemporary linguistic reality. The study identified a number of attributes specific to humans in Tahdhib al-Lugha and documented them from their narrators. It also found that the semantic significance of many terms has remained unchanged up to the present time, owing to al-Azharī's precision in transmitting from narrators or his direct oral consultation with the Arabs. Furthermore, the study highlighted the passages in Tahdhib al-Lugha where scholars judged the attributes as being specific, using expressions denoting particularization—such as